Confronting molecular rotors and self-quenched dimers as fluorogenic BODIPY systems to probe biotin receptors in cancer cells. Issue 39 (16th April 2021) - Fam, Kyong T.; Saladin, Lazare; Klymchenko, Andrey S.; Collot, Mayeul
Abstract : Two fluorogenic systems based on BODIPY have been confronted as probes for biotin receptor in live cells. The self-quenched dimer that lights up in the non-polar membrane was found to be more efficient than the viscosity-sensitive molecular rotor. Abstract : Probing receptors at the cell surface to monitor their expression level can be performed with fluorogenic dyes. Biotin receptors (BRs) are particularly interesting as they are overexpressed in cancer cells. Herein, to image BRs, we adapted and systematically compared two fluorogenic systems based on BODIPYs: a molecular rotor and a self-quenched dimer that light up in response to high viscosity and low polarity of the membrane, respectively. The fluorogenic dimer proved to be more efficient than the rotor and allowed BRs to be imaged in cancer cells, which can effectively be discriminated from non-cancer cells.